Child Protection Centers and Forensic Medicine Approach - Kafadar, Huseyin (Derman Medical Publ, 2014)
According to the World Health Organization (WHO) anyone under the age of 18 is determined as child. Child abuse is described by Henry Kempe in 1962. Nowadays, neglect definition and prevention for children are most important. Child maltreatment is defined as harmful behaviors on physical, emotional, mental, or sexual health of child. There are two ways of maltreatment; abuse and neglect according to the forensic medicine approach. The aim of this study is to discuss Child Protection Center, the center service delivery and forensic medicine approach.
Keywords: Forensic Medicine; Child Abuse